Role of the Bible in the development of languages and linguistics. An outline of the issue - Walczak, Bogdan (Forum Lingwistyczne, 2015)
Role of the Bible in the development of languages and linguistics. An outline of the issue The paper describes a very significant role of Bible translation in the development of the Slavic national languages. The author focuses on the Polish language which in its literary form was shaped in the Middle Ages but its full functional efficiency was reached in the 16th century. Among the medieval relics, the translation of psalms and other Bible passages played a great cultural role. However, the complete Polish translations of the Holy Bible appeared in the 16th century (Biblia Budnego, Leopolity, Wujka). Those renditions enriched the Polish language with a number of new words. Moreover, they provoked a scientific reflection on the Slavic languages. As a result, the author proposes a thesis asserting that the act of Bible philological translations contributed to further linguistic research. Key words: history of language, Bible, development of language, linguistics<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />